2019
DOI: 10.1161/circulationaha.118.037454
|View full text |Cite
|
Sign up to set email alerts
|

Relative Prognostic Importance and Optimal Levels of Risk Factors for Mortality and Cardiovascular Outcomes in Type 1 Diabetes Mellitus

Abstract: Background: The strength of association and optimal levels for risk factors related to excess risk of death and cardiovascular outcomes in type 1 diabetes mellitus have been sparsely studied. Methods: In a national observational cohort study from the Swedish National Diabetes Register from 1998 to 2014, we assessed relative prognostic importance of 17 risk factors for death and cardiovascular outcomes in individuals with type 1 diabetes mellitus. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 24 publications
6
93
2
11
Order By: Relevance
“…Notably, we found that those with normal AER and microalbuminuria with RH had 3.5 times higher risk of stroke, compared with those who had controlled BP. It is well known that hypertension is one of the strongest risk factors for stroke, both in the general population (35) and in type 1 diabetes (19, 36). The risk of stroke increases after BP exceeds 130/80 mmHg in individuals with type 2 diabetes (37), while among individuals with type 1 diabetes a linear increase in systolic BP is observed even earlier (19).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that those with normal AER and microalbuminuria with RH had 3.5 times higher risk of stroke, compared with those who had controlled BP. It is well known that hypertension is one of the strongest risk factors for stroke, both in the general population (35) and in type 1 diabetes (19, 36). The risk of stroke increases after BP exceeds 130/80 mmHg in individuals with type 2 diabetes (37), while among individuals with type 1 diabetes a linear increase in systolic BP is observed even earlier (19).…”
Section: Discussionmentioning
confidence: 99%
“…La duración de la diabetes es uno de los predictores más importantes para infarto agudo de miocardio (IAM), junto con el colesterol de lipoproteínas de baja densidad (cLDL) y HbA1c. El desarrollo de DM1 antes de los 10 años de edad se asocia con un riesgo 90 veces mayor de IAM en mujeres y 30 veces mayor de ECV hacia los primeros años de su vida adulta generando una pérdida de años de vida de 17,7 y 14,2 en mujeres y hombres con DM1 respectivamente 8,9,10,11 (Figura 1).…”
Section: Epidemiología De La Enfermedad Cardiovascular En Personas Counclassified
“…La HbA1c y la albuminuria son los predictores más importantes de mortalidad y ECV. La duración de la diabetes, la albuminuria y la PAS tienen interacciones estadísticamente significativas con HbA1c 9,10,11 . 1) Control glucémico.…”
Section: Factores De Riesgo Tradicionalesunclassified
See 1 more Smart Citation
“…La principal causa de muerte en personas con DM1 es de origen cardiovascular. Si bien la mortalidad en personas con DM1 disminuyó significativamente en los últimos 40 años debido al mejor manejo de factores glucémicos y no glucémicos, el riesgo de muerte por todas las causas y cardiovascular en DM1 con inadecuado control glucémico es ocho a 10 veces mayor que en la población general 7,8,9 . El primer evento cardiovascular (CV) en DM1 ocurre en promedio 10 a 15 años antes que en personas sin DM 10 .…”
Section: Enfermedad Cardiovascular Y Diabetesunclassified